Effect of Corrective Exercises According to the Biomechanical Indicators of the Footprint of the Paraplegic (Medico Legal Update, 2020)
The value of scientific research depends on the type of data and the accuracy and quality of the devices usedin these devices and foot scanner (foot scan), a device for the analysis of walking movements and helps inthe detection of the values of many variables of the amount of pressure and the deviation and deviation ofthe foot and direction and time of contact and the extent of benefit Of these variables in the identificationof errors and the development of appropriate exercises appropriate to them and this is what the importanceof research as a serious attempt to identify the current mechanical situation of this category of disabledand study the details of this case and the problem of research is the lack of appropriate corrective exercisesand the objective of the research to design corrective exercises and knowledge of their effect on somevalues of the biomechanical variables of the footprint at a speed of (2 km / h). Corrective exercises Ledto an improvement in the level of walking of the sample by the development of the values of the variablesinvestigated.